Comparison of Master of Science in Critical Care Nursing Curriculum in Iran and Master of Science in Critical Care in the University of Glasgow: A Comparative Study - Hamideh Ebrahimi; Masoumeh Ebrahimi; Meimanat Hosseini (Shahid Sadoughi University of Medical Sciences, 2022)
Background: The main purpose of a health system is to provide quality care services, and providing orderly, high-quality, safe, and economic services requires skillful and knowledgeable nurses. Critical Care M.Sc. curriculum in Iran was revised in June 2010. Studies show   that, since specialized associations such as the World Health Organization have demanded the improvement of educational standards for the graduates of this major, educational planner have tried to design a successful and efficient curriculum through examining other successful educational systems in the world. By comparing different educational systems, quality of educational programs can be improved. In addition, comparative studies are one of the most dynamic scientific approaches adopted by educational planners in various countries, such that it is considered a prerequisite for designing modern educational systems. In light of this, the present study tried to compare Critical Care M.Sc. curriculum in Iran with that of the university of Glasgow. It is one of the oldest universities in the UK, the fourth oldest and of the top 100 universities in the world. Methods: This was a comparative and descriptive study conducted in 2020 to compare the Critical Care M.Sc. curriculum in Iran with a corresponding one in the university of Glasgow through Beredy model. Results: Although Critical Care M.Sc. Curriculum in Iran is in an acceptable position compared to the university of Glasgow's evidence-based education approach, the focus on academic writing skills for improving the graduates' skill of writing research papers, and the availability of a part time program were of the advantages of Critical Clinical Care curriculum at the university of Glasgow. On the other hand, lack of a specific and strategic programing, and ambiguities about missions of the graduates were the weaknesses. The curriculum in Iran was clear about the philosophy, mission, and perspective, while job opportunities of the graduates in clinical settings were not clear. This was one of the reasons for the reluctance of the graduates to enter clinical environment, which was a disadvantage of the program in Iran. Conclusion: Although Critical Care M.S Curriculum in Iran is in an acceptable position compared to the one in the University of Glasgow's evidence-based approach, Focus on the academic writing skills for improving the graduates' skills of writing research papers, and availability of a part time program were of the advantages of the critical clinical care program at the University of Glasgow. On the other hand, lack of a strategic programing and the ambiguities about missions of the graduates were the weaknesses. The curriculum in Iran was clear about the philosophy, mission, and perspective, while the job opportunities of the graduates in clinical setting were not clear. This is one of the reasons for the reluctance of graduates to enter clinical environment, which is a disadvantage of the program in Iran